Progressive Neuropsychiatric Symptoms Following Recurrent COVID-19 Infections in a Previously Healthy Adolescent - Shawl, Christopher; Clark, R. Hunter; Edwards, Matthew T.; Berson, Casey; Zappitelli, Megan (Case Reports in Psychiatry, 2023)
This is the almost 2-year-long course of a 16-year-old male without significant psychiatry history who abruptly developed symptoms of obsessive-compulsive disorder (OCD) and psychosis following a confirmed coronavirus disease 2019 (COVID-19) infection. His symptoms worsened following a confirmed reinfection with COVID-19. He responded poorly to treatment with selective serotonin reuptake inhibitors, antipsychotics, and benzodiazepines. This case highlights an emerging phenomenon of post-COVID-19 neuropsychiatric sequelae and presents a complicated diagnostic and treatment challenge. The differential for this patient was explored and outlined in detail, and the medical workup recommendations for new-onset mental status changes were reviewed as they pertain to the patient’s assessment and treatment course. While there are several case reports of adolescents with abrupt-onset OCD and psychosis symptoms following COVID-19 infections, none of these reports include worsening of symptoms following reinfection, and few reports follow patients beyond initial hospitalization and treatment.